Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Rénover la pratique de l’éducation à la sexualité des personnes ayant des incapacités intellectuelles - Dupras, André (Nouvelles pratiques sociales, 2013)
La reconnaissance du droit des personnes ayant des incapacités intellectuelles à une éducation à la sexualité a généré la conception et l’implantation de programmes éducatifs. À quelles valeurs et croyances les professionnels se réfèrent-ils pour organiser l’éducation à la sexualité? Une analyse critique des approches dominantes actuelles est proposée pour contribuer à leur progrès et à leur transformation. Pour dépasser les limites des approches paternalistes et objectivistes, il est suggéré d’adopter un nouveau paradigme fondé sur des perspectives participatives et subjectivistes. Le renouvellement de l’éducation à la sexualité pourrait procéder par énovation en enrichissant et en élargissant les pratiques existantes.
Keywords: amérique du nord; amériques; approches et analyses; canada; capacitisme; discipline; intervention sociale; québec; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Par les mains pour les yeux : les représentations de l'identité sourde au sein de performances artistiques de la scène montréalaise - Paradis-Vigneault, Marie-Claude (Université Laval, 2012)
Ce mémoire s’appuie sur une recherche ethnographique réalisée principalement au sein de la communauté sourde de Montréal et tente de déceler les représentations de l’identité sourde au sein de performances artistiques de la scène montréalaise. Le but de cette recherche est d’inscrire la culture sourde dans les réflexions sociales et scientifiques portant sur l’expression identitaire de minorités culturelles par les arts. Afin de démontrer les liens à la fois théoriques et pratiques entre l’identité sourde et celles de minorités socio- politiques, telles que les Noirs, les gays, les femmes ou les Queers, cette étude s’appuie sur les concepts de performativité (Judith Butler), de performance (Clifford Geertz et Victor Turner) et de représentations (Stuart Hall et Serge Moscovici). Y seront également démontrées les relations entre ces notions, le vécu des sujets, leur agency et leur expression artistique.
Keywords: amériques; anthropologie; approches et analyses; capacitisme; danse; discipline; histoire et politique; montréal; mémoires/thèses; performativité; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; théâtre; étude qualitative

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis